Tanzania Skills for Competitiveness in the Small and Medium Enterprise Sector - Sabarwal, Shwetlena (World Bank, Washington, DC, 2014)
We examine the question of workforce skills for small and medium enterprises (SMEs) in Tanzania and find a mixed picture full of potential. On the one hand, education access has expanded at all levels and a more educated cohort is now entering the labor market - signaling the availability of a more skilled workforce for SMEs. On the other hand, acute shortages of secondary and postsecondary graduates persist. Disturbingly, the quality and relevance of primary education has come into question. It is unclear whether increased access to primary education is actually translating into acquisition of crucial basic skills in the country. In light of this, it is unsurprising that education attainment no longer appears to be a reliable proxy for relevant skills, as perceived by employers. Further, SMEs seem to have very little meaningful connection with education institutions for recruitment of workers. A related but equally concerning problem relates to the culture of recruitment among SMEs in Tanzania. It is one of passive hiring, wherein firms rely on networks and referrals to identify employees instead of actively seeking them through open advertising and links with education providers. In this backdrop there is room for cautious optimism. SMEs seem increasingly to realize and emphasize the importance of workforce skills, even though, in relative terms, they are likely to be significantly more pre-occupied with infrastructure constraints. Interestingly, a large share of firms that have recently failed consider inadequate workforce skills to be a contributing factor of above average importance to firm failure.